On the taxonomy of the genus Barsochrista Singh & Kirti, 2016 (Lepidoptera, Erebidae, Arctiinae) - Volynkin, Anton V.; Ivanova, Maria S. (Zootaxa, 2017)
The Asura / Miltochrista generic complex is one of the largest and taxonomically most difficult Lithosiini groups, including several hundreds of species, most of which occur in the Oriental Tropics. At present the complex includes about 25 valid genera as well as several generic taxa of unclear status, and some species groups not established taxonomically that probably represent distinct genera or subgenera (Holloway 2001; Kirti & Singh 2016; Volynkin 2016).